Integrating Evaluation and Agent-Based Modeling: Rationale and an Example for Adopting Evidence-Based Practices - Morell, Jonathan A.; Hilscher, Rainer; Magura, Stephen; Ford, Jay (Journal of MultiDisciplinary Evaluation, 2010)
<!– [if gte mso 9]> <![endif]–><!– [if gte mso 9]> Normal 0 false false false EN-US X-NONE X-NONE <![endif]–><!– [if gte mso 9]> <![endif]–><!– /* Style Definitions */ p.MsoNormal, li.MsoNormal, div.MsoNormal mso-style-unhide:no; mso-style-qformat:yes; mso-style-parent:""; margin:0in; margin-bottom:.0001pt; mso-pagination:widow-orphan; font-size:11.0pt; mso-bidi-font-size:12.0pt; font-family:"Times New Roman","serif"; mso-fareast-font-family:"Times New Roman"; mso-bidi-font-family:Arial; .MsoChpDefault mso-style-type:export-only; mso-default-props:yes; font-size:10.0pt; mso-ansi-font-size:10.0pt; mso-bidi-font-size:10.0pt; @page Section1 size:8.5in 11.0in; margin:1.0in 1.0in 1.0in 1.0in; mso-header-margin:.5in; mso-footer-margin:.5in; mso-paper-source:0; div.Section1 page:Section1; –><!– [if gte mso 10]> <![endif]–><!– [if gte mso 9]> <![endif]–><!– [if gte mso 9]> Normal 0 false false false EN-US X-NONE X-NONE <![endif]–><!– [if gte mso 9]> <![endif]–><!– /* Font Definitions */ @font-face font-family:"Cambria Math"; panose-1:2 4 5 3 5 4 6 3 2 4; mso-font-charset:0; mso-generic-font-family:roman; mso-font-pitch:variable; mso-font-signature:-1610611985 1107304683 0 0 159 0; @font-face font-family:Georgia; panose-1:2 4 5 2 5 4 5 2 3 3; mso-font-charset:0; mso-generic-font-family:roman; mso-font-pitch:variable; mso-font-signature:647 0 0 0 159 0; /* Style Definitions */ p.MsoNormal, li.MsoNormal, div.MsoNormal mso-style-unhide:no; mso-style-qformat:yes; mso-style-parent:""; margin:0in; margin-bottom:.0001pt; mso-pagination:widow-orphan; font-size:11.0pt; font-family:"Arial","sans-serif"; mso-fareast-font-family:"Times New Roman"; .MsoChpDefault mso-style-type:export-only; mso-default-props:yes; mso-fareast-language:ZH-TW; @page WordSection1 size:8.5in 11.0in; margin:1.0in 1.0in 1.0in 1.0in; mso-header-margin:.5in; mso-footer-margin:.5in; mso-paper-source:0; div.WordSection1 page:WordSection1; –><!– [if gte mso 10]> <![endif]–> Background: While there is a great deal of discussion about complex adaptive systems in the field of evaluation, little has been written about the expression of complex adaptive systems in terms of agent-based models, the execution of those models as computer simulations, or the tight integration of agent-based modeling with traditional evaluation methods. These topics need to be explored if evaluation is to move beyond using complex adaptive systems in an exclusively heuristic fashion. Purpose: This paper advocates for the integration of agent based modeling into traditional evaluation activities. We advance this position in order to spark a movement toward incorporating the formal application of complex adaptive systems into the theory and methods of evaluation. To make our case, we provide a hypothetical example of how interactions between an agent-based model and evaluation can provide unique and powerful understanding about the adoption of evidence-based practices in the field of addiction treatment. We advance our argument by addressing four questions: Why combine evaluation methods with simulation methods? Why use a complex adaptive systems approach? Why add agent-based modeling to the mix of evaluation tools? What is the relationship between agent-based modeling and the theories and methods of evaluation that are being developed to deal with surprise, unintended consequences, and program evolution? Setting: Not applicable. Intervention: Not applicable. Research Design: Not applicable. Data Collection and Analysis: Not applicable. Findings: Not applicable.